‘RS Gaúcho’: new black bean cultivar with high productivity - Juliano Garcia Bertoldo; Rodrigo Favreto; Raquel Paz da Silva; Liege Camargo da Costa; Rogério Ferreira Aires; Nilton Luis Gabe; Coralia Maria Oliveira Medeiros; Marcelo de Carli Toigo; Sérgio Dias Lannes (Pesquisa Agropecuária Gaúcha)
RS Gaúcho is a common bean cultivar (Phaseolus vulgaris L.) from the black commercial group, with an average weight of 1,000 grains of 186 g, erect habit, indeterminate growth habit, type II/III, 90-day cycle, and an average productivity of 2,308 kg ha-1. The development of the RS Gaúcho cultivar is in line with the theme of agricultural sustainability, as this new cultivar presents excellent productivity. It is indicated for different cultivation systems in the State of Rio Grande do Sul, in the harvest (1st harvest) and off-season (2nd harvest) periods, in dry or irrigated crops, in direct or conventional planting systems, in monoculture or intercropping.